2020
DOI: 10.1111/jfpp.14852
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effects of high hydrostatic pressure on physicochemical, thermal, and structural properties of maize, potato, and sweet potato starches

Abstract: Maize (Zea mays L.), potato (Solanum tuberosum L.) and sweet potato (Ipomoea batatas [L.] Lam.) are important cereal, tuber, and root crops, respectively, which are the most widely used in the world. They are playing pivotal roles in starch production, and are extensively contributing to the food and other industries. Starch is not only being used as a good source of food to provide energy for humans and animals, but also being widely used in textile, medicine, papermaking, casting, metallurgy, petroleum, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…High hydrostatic pressure has been effectively used to prolong the shelf life of food products with the least impact on their taste, nutrition, and aroma (Huang et al, 2017). Effects of high hydrostatic pressure (100, 300, and 500 MPa for 15 and 30 min at 25 °C) on thermal properties of maize, potato, and sweet potato starches (20%, w/w) were investigated by Rahman et al (2020). It was observed that the effect of high hydrostatic pressure on starch is a function of molecular structure.…”
Section: Non-thermal Physical Modification Of Starchmentioning
confidence: 99%
“…High hydrostatic pressure has been effectively used to prolong the shelf life of food products with the least impact on their taste, nutrition, and aroma (Huang et al, 2017). Effects of high hydrostatic pressure (100, 300, and 500 MPa for 15 and 30 min at 25 °C) on thermal properties of maize, potato, and sweet potato starches (20%, w/w) were investigated by Rahman et al (2020). It was observed that the effect of high hydrostatic pressure on starch is a function of molecular structure.…”
Section: Non-thermal Physical Modification Of Starchmentioning
confidence: 99%
“…According to their results, quinoa starch had lower swelling power than maize starch because quinoa starch had lower amylose content than maize starch. Rahman et al ., (2020) showed that treatment time showed a significant effect on the solubility and swelling power of maize, potato and sweet potato starch. The lowest solubility was found for maize starch, while the lowest swelling power was found for potato starch.…”
Section: Physicochemical Properties Of Hhp‐treated Starches During Gelatinisationmentioning
confidence: 99%
“…Rahman et al. (Rahman et al ., 2020) reported that changing intensity of peaks at 1020–1160 cm –1 for potato starches was explained by starch gelatinisation. It was observed that there was a significant decrease in peak height at 500 MPa treatment.…”
Section: Physicochemical Properties Of Hhp‐treated Starches During Gelatinisationmentioning
confidence: 99%
“…High hydrostatic pressure (HHP) is an emerging technology that has been used to physically modify starch-water suspensions. The demand for natural ingredients, equivalent to the desire for a socalled clean label, gives a physical method such as HHP an advantage over chemical and enzymatic methods in the modification of starch, as there is no use of reagents or production of waste residues (Rahman et al, 2020). The main effect of HHP is proposed to be on non-covalent bonds and may affect amorphous and crystalline regions of the starch granules, dependent on the botanical source and process conditions.…”
mentioning
confidence: 99%
“…The effect of HPP method to physically modify dispersions of starch from different botanical sources has been well documented, such as: wheat (Hu et al, 2017), maize (Li & Zhu, 2018;Rahman et al, 2020), rice (Deng et al, 2014;Li et al, 2012), sorghum , barley (Stolt et al, 2000), pseudocereals (Ahmed et al, 2018;Li et al, 2016;, potato (Błaszczak et al, 2005;Rahman et al, 2020), cassava (Lertwanawatana et al, 2015), sweet potato (Rahman et al, 2020), beans (Li et al, 2011(Li et al, , 2015, pea (Leite et al, 2017), lentil (Ahmed et al, 2016), and other sources. Although Stute et al (1996) reported the first and, so far, only findings about a HHP effect on arrowroot starch, the present work is the first report of a detailed study correlating structural changes with the applications of arrowroot starch as raw material.…”
mentioning
confidence: 99%